Impact of Asymptomatic Flatfoot on Clinical and Radiographic Outcomes of the Modified Lapidus Procedure in Patients With Hallux Valgus. Issue 2 (May 2022) - Rajan, Lavan; Kim, Jaeyoung; Fuller, Robert; Cororaton, Agnes; Mizher, Rami; Srikumar, Syian; Ellis, Scott J.
Background: Patients with hallux valgus commonly present with concomitant flatfoot deformity. First-ray hypermobility, among other biomechanical factors, has been suggested as a potential link between these deformities. However, not all hallux valgus patients exhibit symptoms associated with flatfoot deformity, and the necessity of correcting the asymptomatic flatfoot at the time of hallux valgus correction is unclear. We aimed to investigate the relationship between asymptomatic flatfoot and patient-reported and radiographic outcomes after the Lapidus procedure. Methods: This study included 142 patients who underwent the Lapidus procedure for hallux valgus at a single institution. Sixty-one patients met radiographic criteria for flatfoot. No patients exhibited symptoms related to flatfoot deformity on review of clinical notes. Preoperative, minimum 1-year postoperative, and change in Patient-Reported Outcomes Measurement Information System (PROMIS) scores between asymptomatic flatfoot and control groups were compared. Radiographic outcomes including hallux valgus angle (HVA), intermetatarsal angle (IMA), Meary angle, talonavicular coverage angle (TNCA), and calcaneal pitch (CP) were compared. Results: Preoperatively, the flatfoot group had higher BMI 22.6 vs 24.6 ( P < .01) and IMA 15.32 vs 14.0 degrees ( P < .05). Both groups demonstrated preoperative to postoperative improvement in PROMIS physical function ( P < .01), pain interference ( P < .001), pain intensity ( P < .001), and global physical health ( P < .001). There were no preoperative or postoperative differences in PROMIS scores between groups. Postoperatively, there were no differences in HVA or IMA between groups; however, the flatfoot group exhibited greater deformity in Meary angle, TNCA, and CP (all P < .001). Conclusion: There were no significant postoperative differences in patient-reported outcomes of the Lapidus procedure between patients with and without asymptomatic flatfoot, and both groups achieved similar radiographic correction of their hallux valgus deformity. The Lapidus procedure appears to be a reasonable surgical option for hallux valgus correction in patients with asymptomatic flatfoot deformity. Level of Evidence: Level III, retrospective cohort study.